Concomitant administration of proton pump inhibitors does not significantly affect clinical outcomes in metastatic breast cancer patients treated with ribociclib. (December 2022) - Del Re, Marzia; Crucitta, Stefania; Omarini, Claudia; Bargagna, Irene; Mongillo, Marta; Palleschi, Michela; Stucci, Stefania; Meattini, Icro; D'Onofrio, Raffaella; Lorenzini, Giulia; Biondani, Pamela; De Giorgi, Ugo; et al.
Abstract: Background: Gastric pH changes by proton-pump-inhibitors (PPIs) were found to affect progression-free survival (PFS) in metastatic breast cancer (mBC) patients treated with palbociclib. The current study was aimed at investigating whether the same effect could occur in patients treated with ribociclib. Patients and methods: Patients with hormone-positive/HER-2-negative mBC candidates for first-line treatment with ribociclib were enrolled in this retrospective-cohort study. Patients were classified as "no concomitant PPIs" or "concomitant PPIs"; PPI administration covered the entire or not less than 2/3 of treatment with ribociclib. All clinical interventions were made according to clinical practice. Results: A total of 128 patients were consecutively enrolled in the study; 78 belonged to the "no concomitant PPIs" group and 50 to the "concomitant PPIs" group. One hundred and six patients were endocrine-sensitive and received ribociclib and letrozole, while 22 were endocrine-resistant and were treated with ribociclib and fulvestrant. The most prescribed PPI was lansoprazole. According to PFS, patients taking PPIs had a PFS almost superimposable to those assuming ribociclib and endocrine therapy alone (35.3 vs. 49.2 months, p = 0.594). No difference in PFS was observed in estrogen-sensitive or estrogen-resistant mBC in the presence or absence of concomitant PPI treatment (p = 0.852). No correlation with adverse events was found including grade>2 hematological toxicities. Conclusions: The present study supports the hypothesis that the concomitant use of PPIs does not compromise the efficacy of ribociclib in a real-life setting. Highlights: Changes of gastric pH by PPIs may significantly affect the bioavailability of tyrosine kinase inhibitors . Our findings support the hypothesis that long-term treatment with PPI does not compromise the efficacy of ribociclib. Consistent with our results, data from the literature show no effect of gastric pH changes on ribociclib pharmacokinetics.